2006
DOI: 10.1074/jbc.m508829200
|View full text |Cite|
|
Sign up to set email alerts
|

G Protein-induced Trafficking of Voltage-dependent Calcium Channels

Abstract: Calcium channels are well known targets for inhibition by G protein-coupled receptors, and multiple forms of inhibition have been described. Here we report a novel mechanism for G protein-mediated modulation of neuronal voltage-dependent calcium channels that involves the destabilization and subsequent removal of calcium channels from the plasma membrane. Imaging experiments in living sensory neurons show that, within seconds of receptor activation, calcium channels are cleared from the membrane and sequestere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 35 publications
(38 reference statements)
4
24
1
Order By: Relevance
“…S5). These results are not qualitatively different from those that we have previously obtained using rhodamine-conjugated -conotoxin GVIA (8).…”
Section: R E T R a C T E D R E T R A C T E Dcontrasting
confidence: 37%
See 4 more Smart Citations
“…S5). These results are not qualitatively different from those that we have previously obtained using rhodamine-conjugated -conotoxin GVIA (8).…”
Section: R E T R a C T E D R E T R A C T E Dcontrasting
confidence: 37%
“…Dunlap and Fischbach (7) have suggested that transmitter-mediated shortening of the duration of the action potential could be due to a decrease in the number of voltage-dependent calcium channels at the membrane. Recently we have reported an additional mechanism by which 7TMRs can regulate neuronal calcium levels that involves a rapid internalization of voltage-dependent calcium channels into clathrin-coated vesicles upon receptor activation (8). Here we demonstrate that ␤-arrestin 1 is associated with Ca v 2.2 channels and that activation of 7TMRs results in the formation of an arrestin-receptor-channel complex.…”
Section: Inhibition Of Voltage-dependent Calcium Channels By Seventramentioning
confidence: 66%
See 3 more Smart Citations